2014
DOI: 10.1080/19443994.2014.977954
|View full text |Cite
|
Sign up to set email alerts
|

Performance of wastewater sludge modified with zinc oxide nanoparticles in the removal of methylene blue from aqueous solutions

Abstract: A B S T R A C TThe presence of chromogenic substances in water can potentially be carcinogenic and mutagenic, and thus, it may be hazardous to public health. This study was carried out with the objective of investigating the feasibility of using wastewater sludge, modified with zinc oxide nanoparticles, in the removal of the methylene blue (MB) dye from aqueous solution. The stabilization of nanoparticles onto the sludge was performed using the thermal method in order to increase the active adsorption surface.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Zinc oxide nanoparticles, the study of which has been described in this work, can be successfully utilized as vulcanization activators in the rubber industry, UV filters in sunscreen products, antibacterial agents in dermatological drugs, anode materials in lithium‐ion batteries, coating materials for orthopaedic and dental implants, or as catalysts in water purification from multiple pollutions (e.g. from potentially carcinogenic and mutagenic substances like methylene blue) …”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide nanoparticles, the study of which has been described in this work, can be successfully utilized as vulcanization activators in the rubber industry, UV filters in sunscreen products, antibacterial agents in dermatological drugs, anode materials in lithium‐ion batteries, coating materials for orthopaedic and dental implants, or as catalysts in water purification from multiple pollutions (e.g. from potentially carcinogenic and mutagenic substances like methylene blue) …”
Section: Introductionmentioning
confidence: 99%
“…From the Langmuir model, the MBD removal efficiency of the optimized nanocomposites was determined to be 7.75 mg g . 1 The PSO adsorption-reaction kinetics model fits well. These adsorption process tests are showing the domination of monolayer/chemisorption type of adsorption.…”
Section: Resultsmentioning
confidence: 87%
“…The adsorption kinetics study was performed using the adsorbate-adsorbent contact time of 10,30,50,70,90,110,130, and 150 min. Furthermore, the adsorption isotherm test was conducted using MBD concentration of 1,5,10,15,20,25,30, and 35 mg l . 1 For a proper understanding of the adsorption process, the adsorption isotherm models (equations (3)-(8)) and adsorption kinetics models (equations (9)-(13)) were used [21,22].…”
Section: Batch Adsorption Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…for the extraction of dyes from contaminated water [3][4][5]. It was reported that ZnO is an efficient material for dye adsorption [6][7]. It is also a gifted semiconductor material due to its direct wide energy band gap (3.37 eV) with a large exciton binding energy (60 meV) at ambient temperature [7][8][9].…”
Section: Introductionmentioning
confidence: 99%